Knowledge, attitudes, and practices regarding urinary tract infections among women in the United Arab Emirates - Shaikha Salah Alhaj; Sajad Allami; Amjad Mohamadiyeh; Ammar Agha; Abdul Kareem Abu Ali; Joudi M. Bassam Habbal; Balsam Qubais Saeed (PLoS ONE, 2025)
Background Urinary tract infections (UTIs), which are infections of the kidneys, ureters, bladder, or urethra, are a worldwide public health concern. As compared to men, women are more prone to UTIs. There have been several studies that explore the knowledge, attitudes, and practices of women regarding UTIs in different countries, but no such study has been conducted in the UAE; therefore, we conducted this study in the UAE setting. Methods This study was conducted using an online survey created on Microsoft Forms. The minimum sample size required for our study was 385. This study was conducted after obtaining ethical approval from the Research Ethics Committee at the University of Sharjah. A personally designed questionnaire consisting of 21 items, derived from previous research was used to record data. The data was analyzed using SPSS. Results A total of 475 females were included in the study. Most respondents were aged 18–30 years (47.4%). Our study found that a majority of the participants (69.7%) correctly identified bacteria as the most common cause of UTIs. With regards to practices undertaken during UTIs, among the participants with a history of UTI episodes, 32.6% waited 24–48 hours before seeking medical attention at a hospital or clinic, while 10% did not visit a hospital at all. Distinct trends were found when comparing demographic factors with knowledge levels. Most notably, the age group of 18–30 years showed the highest percentage of high-knowledge individuals (49%) compared to other age groups (p < 0.05). Education level was significantly (p = 0.003) associated with UTI knowledge. Going to the hospital/clinic was reported by 41% with high knowledge but only by 20% of those with poor knowledge. Moreover, a higher proportion of individuals with high knowledge sought medical attention immediately within 24 hours (47%). Conclusion Most of the participants possessed adequate knowledge regarding UTIs. Higher knowledge levels were associated with more proactive and appropriate health behaviors, such as seeking medical attention promptly and drinking more water.